Green Remediation of Carbamazepine from Water Using Novel Magnetic Iron Modified Carbonized Baggasse: Kinetics, Equilibrium and Mechanistic Studies - Okello, Veronica A.; Kimosop, Selly J.; Getenga, Zakari M.; Orata, Francis; Shikuku, Victor O. (SCIENCE DOMAIN, 2017)
Baggasse derived biochar magnetically modified with iron (α-Fe2O3-CBG) was fabricated, characterized and applied as a low-cost adsorbent for the removal of carbamazepine (CBZ), a pharmaceutically active compound which has been reported as an emergent water contaminant. Characterization of the synthesized (α-Fe2O3-CBG) composite showed that iron was effectively impregnated onto the carbonized bagasse network. The composite was able to achieve 60.9 % CBZ removal within a period of 4 hours. The time-dependency adsorption data followed the pseudosecond order kinetic law while the intraparticle diffusion model indicated that pore diffusion is not the sole operative rate-determining mechanism with significant boundary layer effects. Freundlich model best explained the equilibrium sorption data. The adsorption extent was also strongly pH-dependent though adsorption mechanism is significantly driven by electrostatic interactions at lower pH. Furthermore, magnetic separation of the contaminant-laden adsorbent was successfully accomplished.
Keywords: Carbamazepine; Adsorption